Magnetic iron oxide nanoparticles as novel and efficient tools for atherosclerosis diagnosis - Montiel Schneider, María Gabriela (2017)
Cardiovascular complications derivate from atherosclerosis are the main cause of death in western world. An early detection of vulnerable atherosclerotic plaques is primordial for a better care of patients suffering the pathology. In this context nanotechnology has emerged as a promising tool to achieve this goal. Nanoparticles based on magnetic iron oxide (MNPs) have been extensively studied in cardiovascular diseases diagnosis, as well as in the treatment and diagnostic of other pathologies. The present review aims to describe and analyze the most current literature regarding to this topic, offering the level of detail required to reproduce the experimental tasks providing a critical input of the latest available reports. The current diagnostic features are presented and compared, highlighting their advantages and disadvantages. Information on novel technology intended to this purpose is also recompiled and in deep analyzed. Special emphasis is placed in magnetic nanotechnology, remarking the possibility to assess selective and multifunctional systems to the early detection of artherosclerotic pathologies. Finally, in view of the state of the art, the future perspectives about the trends on MNPs in artherosclerorsis diagnostic and treatment have also been addressed.